Feather-degrading Bacillus cereus HD1: genomic analysis and its optimization for keratinase production and father degradation - Radin Yahaya, Radin Shafierul; Phang, Lai Yee; M. Normi, Yahaya; Abdullah, Janna Ong; Ahmad, Siti Aqlima; Sabri, Suriana (Springer, 2022)
Keratinase is an important enzyme that is used to degrade feather wastes produced by poultry industries and slaughterhouses that accumulate rapidly over time. The search for keratinase-producing microorganisms is important to potentially substitute physicochemical treatments of feather waste. In this study, the genome of Bacillus cereus HD1 and its keratinolytic prowess was investigated. The whole-genome shotgun size is 5,668,864 bp consisting of 6083 genes, 69 tRNAs, and 10 rRNAs. The genomic analyses revealed 15 potential keratinase genes and other enzymes that might assist keratin degradation, such as disulfide reductase and cysteine dioxygenase. The optimal conditions for feather degradation and keratinase production by B. cereus HD1 such as incubation time, pH, temperature, yeast extract, and glycerol concentrations were determined to be 5 days, pH 8, 37 °C, 0.05% (w/v), and 0.1% (v/v), respectively. Under optimized conditions, B. cereus HD1 exhibited feather degradation of 65%, with bacterial growth and maximum keratinase activity of 1.3 × 1011 CFU/mL and 41 U/mL, respectively, after 5 days of incubation in a feather basal medium. The findings obtained from this study may facilitate further research into utilizing B. cereus HD1 as a prominent keratinolytic enzymes production host and warrant potential biotechnological applications.